The walls speak (Journal of Parents and Teachers, 2026)
Since the earliest civilisations, painting has been used to create murals, with colour playing a fundamental role in this form of communication. Inspired by Juan Carlos Langlois' article entitled La ciudad en colores (The City in Colours), published in El Correo de la Unesco, we decided to collect several murals that adorn some of the walls of our schools and parks in the city and which are mainly ecological in nature, in order to use them as a basis for reflection on ecology within the teaching unit entitled ‘Christian Faith and Defence of the Planet’.
Keywords: murals, walls, school, city, ecology, religious education